Supplementation with 45S5 bioactive glass reduces in vivo resorption of the β-tricalcium-phosphate-based bone substitute material Vitoss - Westhauser, Fabian; Essers, Christopher; Karadjian, Maria; Reible, Bruno; Schmidmaier, Gerhard; Hagmann, Sébastien; Moghaddam-Alvandi, Arash (International journal of molecular sciences, 2019)
Compared to other materials such as 45S5 bioactive glass (BG), β-tricalcium phosphate (β-TCP)-based bone substitutes such as Vitoss show limited material-driven stimulation of osteogenesis and/or angiogenesis. The unfavorable degradation kinetics of β-TCP-based bone substitutes may result in an imbalance between resorption and osseous regeneration. Composite materials like Vitoss BA (Vitoss supplemented with 20 wt % 45S5-BG particles) might help to overcome these limitations. However, the influence of BG particles in Vitoss BA compared to unsupplemented Vitoss on osteogenesis, resorption behavior, and angiogenesis is not yet described. In this study, Vitoss and Vitoss BA scaffolds were seeded with human mesenchymal stromal cells before subcutaneous implantation in immunodeficient mice for 10 weeks. Scaffold resorption was monitored by micro-computed tomography, while osteoid formation and vascularization were assessed by histomorphometry and gene expression analysis. Whilst slightly more osteoid and improved angiogenesis were found in Vitoss BA, maturation of the osteoid was more advanced in Vitoss scaffolds. The volume of Vitoss implants decreased significantly, combined with a significantly increased presence of resorbing cells, whilst the volume remained stable in Vitoss BA scaffolds. Future studies should evaluate the interaction of 45S5-BG with resorbing cells and bone precursor cells in greater detail to improve the understanding and application of β-TCP/45S5-BG composite bone substitute materials.